The utility of pathologic examination and comprehensive phenotyping for accurate diagnosis with perinatal exome sequencing. (3rd July 2022) - Swanson, Kate; Norton, Mary E.; Lianoglou, Billie R.; Jelin, Angie C.; Hodoglugil, Ugur; Van Ziffle, Jessica; Devine, Patrick; Sparks, Teresa N.
Abstract: Objective: Exome sequencing (ES) offers the ability to assess for variants in thousands of genes and is particularly useful in the setting of fetal anomalies. However, the ES pipeline relies on a thorough understanding of an individual patient's phenotype, which may be limited in the prenatal setting. Additional pathology evaluations in the pre‐ and postnatal settings can add phenotypic details important for clearly establishing and characterizing a diagnosis. Methods: This is a case series of prenatal ES performed at our institution in which pathology evaluations, including autopsy, dysmorphology examination, histology, and peripheral blood smear, augmented the understanding of the fetal phenotype. ES was performed at our institution and a multidisciplinary panel reviewed and classified the variants for each case. Results: We present four cases wherein pathology evaluations were beneficial for supporting a perinatal diagnosis identified with ES. In each of these cases, pathology findings provided additional data to support a more complete understanding of the relationship between the perinatal phenotype and variants identified with ES. Conclusion: These cases highlight challenges of perinatal ES related to incomplete prenatal phenotyping, demonstrate the utility of pathology evaluations to support diagnoses identified with ES, and further characterize the disease manifestations of specific genetic variants. Key points: What is already known about this subject? Prenatal Exome sequencing (ES) offers the ability to identify single gene disorders that would be missed by traditional karyotype or microarray. What does this study add? This case series highlights the importance of histologic and anatomic pathology examination and complete phenotyping in order to maximize the yield of ES in the prenatal setting.